Strategic Culture: Theoretical Origins and Approaches (قضايا سياسية, 2024)
Since the 1970s, strategic culture has imposed its cultural personality on specialists and theorists in the intellectual arena, and has struggled with the new realism, leaving an impact on the thought of specialists and some realist theorists, as some of them lined up with it to touch them to fill the gaps that occurred and were not addressed by the new realism. This, and the strategic culture did not leave its theorists without intellectual friction, especially in the literature of its generations, which made its growth and maturity healthier than its predecessors, to be a competitor and some say an alternative to realism, especially when they stood on its philosophy in defining and understanding the behavior of countries.